Sensation, mechanoreceptor, and nerve fiber function after nerve regeneration. Issue 6 (7th December 2017) - Krarup, Christian; Rosén, Birgitta; Boeckstyns, Michel; Ibsen Sørensen, Allan; Lundborg, Göran; Moldovan, Mihai; Archibald, Simon J.
Abstract : Objective: Sensation is essential for recovery after peripheral nerve injury. However, the relationship between sensory modalities and function of regenerated fibers is uncertain. We have investigated the relationships between touch threshold, tactile gnosis, and mechanoreceptor and sensory fiber function after nerve regeneration. Methods: Twenty‐one median or ulnar nerve lesions were repaired by a collagen nerve conduit or direct suture. Quantitative sensory hand function and sensory conduction studies by near‐nerve technique, including tactile stimulation of mechanoreceptors, were followed for 2 years, and results were compared to noninjured hands. Results: At both repair methods, touch thresholds at the finger tips recovered to 81 ± 3% and tactile gnosis only to 20 ± 4% ( p  < 0.001) of control. The sensory nerve action potentials (SNAPs) remained dispersed and areas recovered to 23 ± 2% and the amplitudes only to 7 ± 1% ( P  < 0.001). The areas of SNAPs after tactile stimulation recovered to 61 ± 11% and remained slowed. Touch sensation correlated with SNAP areas ( p  < 0.005) and was negatively related to the prolongation of tactile latencies ( p  < 0.01); tactile gnosis was not related to electrophysiological parameters. Interpretation: The recovered function of regenerated peripheral nerve fibers and reinnervated mechanoreceptors may differentially influence recovery of sensory modalities. Touch was affected by the number and function of regenerated fibers and mechanoreceptors. In contrast, tactile gnosis depends on the input and plasticity of the central nervous system (CNS), which may explain the absence of a direct relation between electrophysiological parameters and poor recovery. Dispersed maturation of sensory nerve fibers with desynchronized inputs to the CNS also contributes to the poor recovery of tactile gnosis. Ann Neurol 2017. Ann Neurol 2017;82:940–950